The impact of adenomyosis on IVF outcomes: a prospective cohort study. Issue 2 (19th April 2021) - Higgins, Chloe; Fernandes, Hugo; Da Silva Costa, Fabricio; Martins, Wellington P; Vollenhoven, Beverley; Healey, Martin
Abstract: STUDY QUESTION: Does the presence of adenomyosis in women treated with IVF alter IVF outcomes? SUMMARY ANSWER: Adenomyosis does not significantly alter IVF outcomes when adjusted for confounding factors including maternal age and smoking status. WHAT IS KNOWN ALREADY: Studies evaluating adenomyosis and its impact on infertility, particularly when focusing on IVF, remain controversial. Many studies report that adenomyosis has a detrimental effect on IVF outcomes, however age is strongly related with both the prevalence of adenomyosis and worse reproductive outcomes. STUDY DESIGN, SIZE, DURATION: A prospective cohort study of women undergoing 4002 IVF cycles who had undergone a screening ultrasound assessing features of adenomyosis from 1 January 2016 to 31 March 2018 at a multi-site private fertility clinic. Of these women, 1228 fulfilled the inclusion criteria and commenced an IVF cycle, with a subset of 715 women undergoing an embryo transfer (ET). Women were defined as having adenomyosis if there was sonographic evidence of adenomyosis on ultrasound as per the Morphological Uterus Sonographic Assessment criteria, and were then compared to women without. PARTICIPANTS/MATERIALS, SETTING, METHODS: All women at a private multi-site IVF clinic who underwent a standardised ultrasound to identify features of adenomyosis and also commenced an IVF cycle were assessed for their outcomes. These included clinical pregnancy (defined as the presence of a gestational sac on ultrasound at 7 weeks' gestation), clinical pregnancy loss, number of cancelled cycles, number of useful embryos for transfer or freezing and live birth rates. As a secondary aim, initiated stimulation cycles and those that had an ET were analysed separately to determine when an effect of adenomyosis on IVF might occur: during stimulation or transfer. MAIN RESULTS AND THE ROLE OF CHANCE: When adjusting for confounders, women with and without sonographic features of adenomyosis had no significant differences in most of their IVF outcomes including live birth rates. LIMITATIONS, REASONS FOR CAUTION: Adenomyosis had a detrimental impact on IVF outcomes prior to adjusting for confounding factors. No allowance was made for the possibility that confounding factors may merely reduce the effect size of adenomyosis on IVF outcomes. Second, despite a power calculation, the study was underpowered as not all fresh cycles led to an ET. WIDER IMPLICATIONS OF THE FINDINGS: This is one of the largest studies to evaluate adenomyosis and IVF outcomes, while also importantly adjusting for confounding factors. The results suggest that adenomyosis does not have the detrimental impact on IVF that has previously been suggested, possibly reducing the importance of screening for and treating this entity. STUDY FUNDING/COMPETING INTEREST(S): The study received no external funding. The authors declare no conflicts of interest. TRIAL REGISTRATION NUMBER: ACTRN12617000796381.